Microbial transformation of steroid / Nurulhuda Mazlan - Mazlan, Nurulhuda (2008)
The main goal of this project is to study the ability of three different endophytes: Aspergillus niger (HAB IO R 12), Coniothyrium lunata (HAB 2 RI) and Berkholderia (HAB 11 R3) to transform pregnenolene acetate in three different media without causing harm to environment, animals or even humans. The extracts after one and two weeks of incubation period on a shake table were analyzed by Thin Layer Chromatography (TLC) to determine the significant compound(s). Isolation process by using Preparative TLC was done to purify the interested compound(s). Purified compound(s) was further identified by using Nuclear Magnetic Resonance (NMR) spectrometer.